Construction of Heterocycles via Novel C-1 Building Blocks - Wan, Jie-Ping; Shanshan, Zhong (Current Organic Chemistry, 2015)
C-1 building blocks are ubiquitously employed in organic synthesis. Based on the recent trend in this field, the advances in the synthesis of heterocycles using unconventional C-1 building blocks are highlighted.
Keywords: heterocycle